PENGGUNAAN MULTIMEDIA PEMBELAJARAN INTERAKTIF UNTUK MENINGKATKAN PEMAHAMAN KONSEP GOTONG ROYONG SISWA KELAS IV SD INPRES OEPURA 2 KUPANG - Enjel Baun; Maxsel Koro; Rista Apriliya Devi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This classroom action research aimed to improve fourth-grade students' conceptual understanding of gotong royong through interactive learning multimedia in Pancasila Education at SD Inpres Oepura 2 Kupang. The subjects were 24 fourth-grade students, consisting of 12 male and 12 female students. The study was implemented in two cycles following the stages of planning, action, observation, and reflection. Data were collected through conceptual-understanding tests, teacher and student activity observations, and documentation, then analyzed using quantitative and qualitative descriptive techniques. The findings showed a progressive improvement in students' conceptual understanding. In Cycle I, 14 students (58.33%) achieved the mastery criterion with a mean score of 72.08. After improving the media presentation, contextual examples, group guidance, and reflective activities, Cycle II showed that 22 students (91.66%) achieved mastery with a mean score of 81.88. Teacher activity increased from 69.44% to 97.22%, while student activity increased from 52.77% to 88.89% and 90.27% based on two observers. The results indicate that interactive learning multimedia can effectively support elementary students' understanding of gotong royong by presenting abstract civic values through visual, audiovisual, and interactive learning experiences.